Teaching Criminology and Criminal Justice Challenges for Higher Education - Young, Suzanne; Strudwick, Katie (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book addresses the challenges within teaching Criminology and Criminal Justice, for students studying and academics involved in designing and delivering courses at an undergraduate and postgraduate level. The book highlights a number of contemporary issues through a wide context of themes and reflections of practice. The chapters are arranged in thematic parts: firstly 'the challenges of diversity and inclusion' secondly 'challenges of creating authentic learning environments', and lastly 'the challenge of creating transformative conversation'. These themes discuss different teaching approaches and present materials which address questions relevant for meeting the challenges. The book focuses on the role and impact of teaching Criminology and Criminal Justice in the real world and explores debates which have autonomy in their questioning and overlapping themes. The narratives reflect upon others' experiences and explore transformative learning and innovation in Criminology and Criminal Justice. Suzanne Young is Associate Professor of Criminal Justice in the School of Law at the University of Leeds, UK. She is a Senior Fellow of the Higher Education Academy, Chair of the British Society of Criminology's Learning and Teaching Network, and Co-Director of the Centre for Innovation and Research in Legal Education at the University of Leeds. Suzanne's scholarship interests are in the areas of student engagement, active learning, and technology enhanced learning. Katie Strudwick is Associate Professor of Criminology and Dean of Lincoln Academy of Learning and Teaching (LALT) at the University of Lincoln, UK. As a long-standing member of the British Society of Criminology's Learning and Teaching Network and Senior Fellow of the HEA. Her research focuses upon student engagement, employability and partnerships with Policing, with a specific interest on co-creation and co-development of teaching and learning through Student as Producer.
1. Introduction -- Part 1: The Challenges of Diversity and Inclusion- 2. Exploring the criminology curriculum - reflections on developing and embedding critical information literacy -- 3. Teaching Criminal Justice as Feminist Praxis -- 4. Chapter Teaching 'Race' in the Criminology Classroom: towards an anti-racist pedagogy -- Part 2: The Challenges of Creating Authentic Learning Environments - 5. Chapter Promoting success for all in Criminology: Widening Participation and recognising difference -- 6. Putting the Cyber into Cybercrime Teaching -- 7. Visualising injustice with undergraduate smartphone photography -- Part 3: The Challenges of Creating Transformative Conversations - 8. Transforming Criminology: Strategies for Embedding 'Employability' Across the Criminology Undergraduate Curricula, - 9. Balancing Sympathy and Empathy in an Emotive Discipline -- 10. Reasonably Uncomfortable: Teaching Sensitive Material Sensitively -- 11. Decolonising the Curriculum: who is in the room? - 12. Conclusion: Pedagogical Principles for Criminology and Criminal Justice.
Keywords: Criminology; Critical criminology; Teaching; Human rights; Crime-Sociological aspects; Education, Higher; Research Methods in Criminology; Critical Criminology; Didactics and Teaching Methodology; Human Rights; Crime and Society; Higher Education